Breast Cancer Treatment and Outcomes in Nigeria: A Systematic Review and Meta-analysis - Olayide, Agodirin; Isiaka, Aremu; Ganiyu, Rahman; Samuel, Olatoke; Halimat, Akande; Olalekan, Olasehinde; Julius, Olaogun; Anya, Romanoff (Asian Pacific Journal of Cancer Care, 2023)
Background and Objective: Nigeria has one of the highest age-standardized breast cancer (BC) mortality rates globally and the highest in Africa. Late presentation and diagnosis have been extensively studied as causes of high BC morbidity and mortality, while treatment and outcomes are underreported. We aggregated data on BC treatment and outcomes in Nigeria to identify gaps in research, challenges, and potential targets for future interventions. Materials and Methods: We reviewed articles on female BC management in Nigeria published between 2011 and 2021 to determine the prevalence of different treatment modalities and outcomes. The meta-analytical procedure followed a random effect model. Results: We identified 15 articles reporting on the treatment and outcomes of 3,857 BC patients. The most prevalent treatment modality was chemotherapy alone. The probability of receiving each treatment modality was 85% (95% CI 66-97) for chemotherapy, 62% (95% CI 51-73) for surgery, and 31% (95% CI 8-59) for radiotherapy. Multimodality treatment, including chemotherapy, surgery, and radiation, was administered to 24% (95% CI 10-43) of patients. In studies with available data, nearly half of patients who initiated chemotherapy did not complete the recommended number of doses or received treatments at irregular intervals. The utilization of radiotherapy was five times higher when patients received treatment in centers with radiation facilities. Overall survival estimates were 80% at one year, 43% at two years, and 32% at five years. Patients with early-stage (AJCC I/II) disease survived longer, with a 5-year survival difference of 32% compared to patients with late-stage (AJCC III/IV) disease. Patients receiving multimodality therapy also had longer survival. The three-year survival for patients who received chemotherapy, surgery, and radiotherapy was 68%, whereas it was 43% for patients who received chemotherapy and surgery only. Conclusion: Improving access to complete systemic therapy, surgery, and radiation for breast cancer patients in Nigeria is imperative and should be the target of future interventions.